Análise comparativa entre filtros híbridos aplicados a cicloconversores em uma siderúrgica - Antunes, Hélio Marcos André (2009)
In steel industry that uses the process of hot strip mill, cycloconverter-fed synchronous motors of megawatts nominal power are usually employed. The cycloconverters absorb a distorted current from the electric main, causing voltage distortion in its point of common coupling (PCC) and many problems with respects the electric power quality. A standard solution used for the harmonic mitigation in this application is obtained through the use of composite passive filter. However this is a solution that can cause harmonic resonance, increasing the harmonic distortion in the electrical system and causing overload in the filtering system. In this work a case in a huge steel industry, located at Grande Vitória is presented. Through measurements in the substation of the hot strip mill, the main currents and voltages waveforms are presented, along with the harmonic spectrum, that confirm the existence of harmonic resonance phenomenon. As an expansion of 30% is foreseen in the load of the rolling mill, it becomes necessary a study of the influence in the associated electrical system. This is due to the harmonic amplification phenomenon, that can increase the distortion levels affecting the passive filtering system behavior. A previously developed model of the system under study was used, which allows the representation of the real system with great correlation degree. Using the model, a comparative simulation analysis is done, by simulation, between two topologies of hybrid filters, the series and parallel, with the objective of harmonic filtering and resonance damping. The obtained results show that the series hybrid filter is the topology that allows better damping of harmonic resonance, and improving the characteristics of harmonic compensation in the passive filtering system, with an active filter of low nominal power, when compared to a parallel hybrid filter. However, this structure doesn't have good filtering characteristics in high frequency, function that the parallel hybrid filter can perform, however with an active filter of higher nominal power. Finally, it is shown that a series hybrid filter, consisting in an active filter and a capacitor bank applied in the electrical system of the rolling mill, can provide the same results of harmonic compensation and resonance damping, with an active filter of smaller nominal power, when compared to the traditional hybrid structure, formed by the series association of active and passive filters.